PERSEPSI GURU TERHADAP PENGGUNAAN MODUL AJAR DALAM PEMBELAJARAN DI SMP NEGERI 18 PEKANBARU - Hadriyani, Siti; Jesica, Gita; Ridho, M. Rasyid; Nugraha, Gusnadi; Alfiandra, M. Diki; Simarmata, Eka Santi; Bakar, Abu; Darmawan, M. Ikhsan; Hambali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe teachers’ perceptions of the use of teaching modules in the learning process at SMP Negeri 18 Pekanbaru. The research employed a qualitative descriptive approach. Data were collected through semi-structured interviews with teachers who were directly involved in the development and implementation of teaching modules. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that teachers generally have positive perceptions of the use of teaching modules in the learning process. Teaching modules are perceived as helpful in aligning learning activities with learning objectives, instructional materials, and students’ needs. In addition, the use of teaching modules contributes to teachers’ understanding of students’ individual needs and encourages greater student participation in classroom learning. However, several challenges remain, including limited supporting facilities, large class sizes, and the uneven distribution of training and socialization regarding the use of teaching modules. Teachers also expressed the need for enhanced training opportunities and stronger support from schools, parents, and educational authorities to optimize the implementation of teaching modules.